Burned - Shepard, Sara, 1977- (New York : HarperTeen, 2012)
"It's spring break, and the pretty little liars are trading in Rosewood for a cruise vacation. They want nothing more than to sail into the tropical sunset and leave their troubles behind for one blissful week. But where Emily, Aria, Spencer, and Hanna go, A goes, too. From scuba diving to tanning on the upper deck, A is there, soaking up all their new secrets. Emily is smooching a stowaway. Aria's treasure-hunting partner is a little too interested in her booty. Spencer's going overboard trying to land a new boy. And a blast-or rather, a crash-from Hanna's past could mean rough waters ahead for everyone. The liars better tighten their life jackets. A perfect storm is brewing, and if they aren't careful, A will bury them at sea..." -- Jacket.
Keywords: Secrecy -- Fiction; Conduct of life -- Fiction; Friendship -- Fiction; High schools -- Fiction; Schools -- Fiction